An integrative review of the factors influencing new graduate nurse engagement in interprofessional collaboration. (1st July 2013) - Pfaff, Kathryn; Baxter, Pamela; Jack, Susan; Ploeg, Jenny
Abstract Aim To analyse critically the barriers and facilitators to new graduate nurse engagement in interprofessional collaboration. Background The acculturation of new graduate nurses must be considered in strategies that address the global nursing shortage. Interprofessional collaboration may support the transition and retention of new graduate nurses. Design Whittemore and Knafl's revised framework for integrative reviews guided the analysis. Data sources A comprehensive multi‐step search (published 2000–2012) of the North American interprofessional collaboration and new graduate literature indexed in the CINAHL, Proquest, Pubmed, PsychINFO and Cochrane databases was performed. A sample of 26 research and non‐research reports met the inclusion criteria. Review methods All 26 articles were included in the review. A systematic and iterative approach was used to extract and reduce the data to draw conclusions. Results The analysis revealed several barriers and facilitators to new graduate engagement in interprofessional collaboration. These factors exist at the individual, team and organizational levels and are largely consistent with conceptual and empirical analyses of interprofessional collaboration conducted in other populations. However, knowledge and critical thinking emerged as factors not identified in previous analyses. Conclusion Despite a weak‐to‐moderate literature sample, this review suggests implications for team and organizational development, education and research that may support new graduate nurse engagement in IPC.